Social and Political Activity of Mykyta Bura in the Age of the Second Polish Republic - Serhiy Troyan; Ruslana Davydyuk (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article analyzes the social and political activity of the native of Rivne region, First World War veteran, Mykyta Bura, the cultural and educational aspects of his work, kinds of effort to the Ukrainization of the Orthodox Church of Poland. It was proved that in the first half of the 1920's teacher M. Bura was involved in the development of Prosvita and Volyn co-operation, and received the first experience of work in the organs of the municipality and the district self-government. In the 1930's, sharing the idea of ​​Ukrainian-Polish coexistence, he became one of the organizers of the Volyn Ukrainian Association, "Ridna Hata", developed the "Prosvita's Hut" network, worked in the "Metropolitan Petro Mohyla Society", "Ukrainian School", Goryn sports club, was elected to the Polish Sejm three times. Arrested and imprisoned by Soviet extrajudicial bodies in 1939. Was released as a Polish citizen and entered the Anders' Army. After the war, he emigrated to Great Britain, and later to Canada.